RELATIONSHIP BETWEEN GOVERNANCE STRUCTURE AND REAL EARNINGS MANAGEMENT: EVIDENCE FROM CHINESE LISTED MANUFACTURING COMPANIES - Feng, Mengyuan (2020)
The aim of the study was to establish the relationship between corporate governance structure and real earnings management (REM) for 1307 listed manufacturing firms in China. Data was collected for the period from 2013 to 2019. OLS regression analysis, correlation analysis and descriptive statistics were adopted for analysis.